Leplat, J., François, A. & Bousta, F. (2021) Simplicillium pech-merlensis, a new fungal species isolated of the Pech-Merle show cave. Phytotaxa 521 (2): 80–94. - Leplat, Johann; Francois, Alexandre; Bousta, Faisl (Phytotaxa, 2021)
N/A